Active Controller of Cantilever Beam Excited by Impact Load (Journal of University of Babylon for Engineering Sciences, 2018)
This work investigated the active control system of cantilever beam excited by impact external load. The control design of the system was modeled and simulated by MATLAB program for the cantilever beam using finite element technique. The controller active system used motor attached at fixed end of the beam to control the dynamic response and to give accurate results under external excitation.The natural frequencies of the system obtained were compared with Ansys software and other research results. The comparisons shown good agreement with maximum percentage difference was (0.76)%. It was obtained from the results that the dynamic response for controlled cantilever beam exhibited better observation of the impact load, and the reduction of the overshoot was 80% approximately comparing between control and uncontrolled response for steel and aluminum beam for applied impact load. It obtained that the type of material had large effect on the vibration of the beam.